Critical reflection on the indication for computed tomography: an interdisciplinary survey of risk and benefit management in patients with sepsis - Maria Isabel Opper Hernando; Denis Witham; Ann-Christine Stahl; Peter Richard Steinhagen; Stefan Angermair; Wolfgang Bauer; Friederike Compton; Andreas Edel; Jan Matthias Kruse; York Kühnle; Gunnar Lachmann; Susanne Marz; et al. (Insights into Imaging)
Abstract Objectives To survey physicians’ views on the risks and benefits of computed tomography (CT) in the management of septic patients and indications for and contraindications to contrast media use in searching for septic foci. Methods A web-based questionnaire was administered to physicians at a large European university medical center in January 2022. A total of 371 questionnaires met the inclusion criteria and were analyzed with physicians’ work experience, workplace, and medical specialty as independent variables. Chi-square tests were used for exploratory analysis. Results While physicians with all levels of work experience were included, the largest group (35.0%, n = 130/371) had 3–7 years of experience. Most physicians agreed that the benefits of CT outweigh its potential adverse effects in septic patients (90.5%, n = 336/371). Responders saw the strongest indication for contrast media administration in septic patients for (1) CT examinations of the abdomen (92.7%, n = 333/359) and (2) combined CT examinations of the chest, abdomen, and pelvis (94.1%, n = 337/358). While radiologists were most likely to consider manifest hyperthyroidism an absolute contraindication to contrast media administration (43.8%, n = 14/32), most other groups of physicians opted for appropriate preparation before contrast media administration in this subset of septic patients. Conclusion In this survey, most participating physicians considered CT an essential diagnostic modality to detect an infectious focus in septic patients. Whereas the risk of ionizing radiation was regarded as justifiable by most physicians, different specialties varied in their assessment of the risks of contrast media administration. Key Points Physicians recognize CT as a relevant imaging modality in the diagnostic management of patients with sepsis. There is an interdisciplinary consensus that the use of ionizing radiation is justified in septic patients. There is disagreement about indications for and contraindications to contrast media administration among physicians from different medical specialties. Graphical Abstract